Prediction of gastric pH‐mediated drug exposure using physiologically‐based pharmacokinetic modeling: A case study of itraconazole - Eunsol Yang; Kyung‐Sang Yu; SeungHwan Lee (Wiley, 2023)
Abstract Abnormal gastric acidity, including achlorhydria, can act as a significant source of variability in orally administered drugs especially with pH‐sensitive solubility profiles, such as weak bases, potentially resulting in an undesirable therapeutic response. This study aimed to evaluate the utility of physiologically‐based pharmacokinetic (PBPK) modeling in the prediction of gastric pH‐mediated drug exposure by using itraconazole, a weak base, as a case. An itraconazole PBPK model was developed on the mechanistic basis of its absorption kinetics in a middle‐out manner from a stepwise in vitro‐in vivo extrapolation to in vivo refinement. Afterward, an independent prospective clinical study evaluating gastric pH and itraconazole pharmacokinetics (PKs) under normal gastric acidity and esomeprazole‐induced gastric hypoacidity was conducted for model validation. Validation was performed by comparing the predicted data with the clinical observations, and the valid model was subsequently applied to predict PK changes under achlorhydria. The developed itraconazole PBPK model showed reasonable reproducibility for gastric pH‐mediated exposure observed in the clinical investigation. Based on the model‐based simulations, itraconazole exposure was expected to be decreased up to 65% under achlorhydria, and furthermore, gastric pH‐mediated exposure could be mechanistically interpreted according to sequential variation in total solubility, dissolution, and absorption. This study suggested the utility of PBPK modeling in the prediction of gastric pH‐mediated exposure, especially for drugs whose absorption is susceptible to gastric pH. Our findings will serve as a leading model for further mechanistic assessment of exposure depending on gastric pH for various drugs, ultimately contributing to personalized pharmacotherapy.